Point-of-care detection of Tannerella forsythia using an antigen–antibody assisted dielectrophoretic impedance measurement method. (May 2015) - Ishii, Yoshihito; Imamura, Kentaro; Kikuchi, Yuichiro; Miyagawa, Satoshi; Hamada, Ryo; Sekino, Jin; Sugito, Hiroki; Ishihara, Kazuyuki; Saito, Atsushi
Abstract: The importance of periodontal treatment planning based on diagnosis with clinical detection of periodontal pathogens has been well recognized. However, reliable detection and quantification methods that can be conveniently used at chair-side have yet to be developed. This study aimed to evaluate the clinical use of a novel apparatus which uses an antigen–antibody reaction assisted dielectrophoretic impedance measurement (AA-DEPIM) for the detection of a prominent periodontal pathogen, Tannerella forsythia . A total of 15 patients with a clinical diagnosis of chronic periodontitis, three periodontally healthy volunteers and two with gingivitis were subjected to clinical and microbiological examinations. Saliva samples were analyzed for the presence of T. forsythia using AA-DEPIM, PCR-Invader and real-time PCR methods. The measurement values for total bacteria and T. forsythia using the prototype AA-DEPIM apparatus were significantly greater in periodontitis group than those in healthy/gingivitis group. Using the AA-DEPIM apparatus with tentative cut-off values, T. forsythia was detected for 14 (12 with periodontitis and 2 either healthy or with gingivitis) out of 20 individuals. The measurement for the detection of T. forsythia by the AA-DEPIM method showed a significant positive correlation with the detection by PCR-Invader ( r  = 0.541, p  = 0.01) and the real-time PCR method ( r  = 0.834, p  = 0.01). When the PCR-Invader method was used as a reference, the sensitivity and specificity of the AA-DEPIM method were 76.5% and 100%, respectively. The results suggested that the AA-DEPIM method has potential to be used for clinically evaluating salivary presence of T. forsythia at chair-side. Trial registration: UMIN Clinical Trials Registry (UMIN-CTR) UMIN000012181. Highlights: We evaluated a novel apparatus for the detection of Tannerella forsythia . The apparatus utilizes an antigen–antibody assisted DEPIM method. This method appears promising for detection of T. forsythia in patients' saliva. AA-DEPIM method may be used effectively as well as conventional PCR-based methods.